2021
DOI: 10.1038/s41436-020-01080-y
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the clinical outcome in CRIM-negative infantile Pompe disease identified via newborn screening: the benefits of early treatment with enzyme replacement therapy and immune tolerance induction

Abstract: Purpose: To assess the magnitude of benefit to early treatment initiation, enabled by newborn screening or prenatal diagnosis, in patients with cross-reactive immunological material (CRIM)-negative infantile Pompe disease (IPD), treated with enzyme replacement therapy (ERT) and prophylactic immune tolerance induction (ITI) with rituximab, methotrexate, and IVIG. Methods: A total of 41 CRIM-negative IPD patients were evaluated. Amongst patients who were treated with ERT+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Surprisingly, within the cohort treated with ERT + ITI, although early treated patients (≤4 weeks) showed a better outcome than late treated, the number of immunotolerant patients (titre ≤6400) did not differ significantly between these groups. However, early treated patients were significantly more likely to remain seronegative than late treated patients [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, within the cohort treated with ERT + ITI, although early treated patients (≤4 weeks) showed a better outcome than late treated, the number of immunotolerant patients (titre ≤6400) did not differ significantly between these groups. However, early treated patients were significantly more likely to remain seronegative than late treated patients [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, ERT did not produce the expected effects in this patient. Very recently, Li et al reported that in CRIM-negative IOPD patients treated with ITI + ERT, the clinical outcomes of the early group (treatment initiation at age ≤4 weeks) were much better than those of the intermediate group (treatment initiation at age >4 and ≤15 weeks) and late group (treatment initiation at age >15 weeks) ( Li et al, 2021 ). In the intermediate group and late group, 66% (10/15) of the patients needed a breathing device during the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of NBS for Pompe disease in the US has been demonstrated with the development of successful screening programs in many states resulting in significant improvements in clinical outcomes for IOPD (Li et al, 2021), yet there remains a challenge in appropriately diagnosing and managing patients with LOPD. This challenge is critically important to address because of the high number of patients with suspected LOPD ascertained via NBS (the vast majority of which do not have a phenotype in the neonatal period) and the large number of these infants with a genotype that includes a VUS or novel variant (Burton et al, 2017b;Klug et al, 2020).…”
Section: Discussionmentioning
confidence: 99%